Аналіз видів захисту особистих даних використовуючи антивірусні програми - Вервейко, В. В.; Чеботарьова, Д. В. (ХНУРЕ, 2021)
The rapid development of information technology is gradually transforming the world. Open and free cyberspace expands the freedom and opportunities of people, enriches society. But there is a downside, which is the theft of personal data, extortion or valuable information. Having anti-virus programs on your personal computer can, if not prevent, severely prevent a fraudster from accessing information that is personal.
Keywords: персональні дані; антивірус; Kaspersky Internet Security